Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.4269/ajtmh.2012.10-0565
|View full text |Cite
|
Sign up to set email alerts
|

Role of Metal Ions on the Activity of Mycobacterium tuberculosis Pyrazinamidase

Abstract: Abstract. Pyrazinamidase of Mycobacterium tuberculosis catalyzes the conversion of pyrazinamide to the active molecule pyrazinoic acid. Reduction of pyrazinamidase activity results in a level of pyrazinamide resistance. Previous studies have suggested that pyrazinamidase has a metal-binding site and that a divalent metal cofactor is required for activity. To determine the effect of divalent metals on the pyrazinamidase, the recombinant wild-type pyrazinamidase corresponding to the H37Rv pyrazinamide-susceptibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 44 publications
(62 reference statements)
0
23
0
Order By: Relevance
“…It has been speculated that the metalloenzyme PZAse of M. tuberculosis coordinates divalent metal ions with the participation of a metallochaperone [26]. We found genes associated to PZA resistance that are related with metal transporting and appeared mutated only in PZA-resistant strains.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…It has been speculated that the metalloenzyme PZAse of M. tuberculosis coordinates divalent metal ions with the participation of a metallochaperone [26]. We found genes associated to PZA resistance that are related with metal transporting and appeared mutated only in PZA-resistant strains.…”
Section: Discussionmentioning
confidence: 79%
“…Metal ions are necessary for PZAse activity and have a direct effect in the PZA antibiotic mechanism [5, 25, 26]. It has been speculated that the metalloenzyme PZAse of M. tuberculosis coordinates divalent metal ions with the participation of a metallochaperone [26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results show that low concentrations of Zn 2ϩ (10 to 80 M) are capable of optimally reactivating PZAse, which has never been shown before. It had previously been reported (38,40) that 1.5 mM Zn 2ϩ was the optimum concentration needed to regain PZAse activity. However, that study did not evaluate as many points in the range of 1 M to 2,000 M Zn 2ϩ as are reported here; the points that coincide with those in this study are consistent.…”
Section: Discussionmentioning
confidence: 78%
“…Metal ions are necessary for PZAse activity and have significant implications for PZA's antibiotic mechanism of action (29,32,(36)(37)(38)(39). M. tuberculosis PZAse is inactivated by the removal of divalent ions and can be differentially reactivated (i.e., enzyme activity can be restored) (38,40); Zhang et al (38) observed reactivation by Fe 2ϩ and Mn 2ϩ when analyzed by inductively coupled plasma-optical emission spectroscopy (ICP-OES), and more recently, Sheen et al (40) showed in vitro reactivation by Co 2ϩ , Mn 2ϩ , and Zn 2ϩ but not Fe 2ϩ , Fe 3ϩ , or Mg 2ϩ . In this study, atomic absorption and X-ray fluorescence assays showed Zn 2ϩ to be present in recombinant PZAse expressed in E. coli (PZAse-EC), and 300 times as much Zn 2ϩ as enzyme was required for PZAse reactivation.…”
mentioning
confidence: 99%